Critical thinking ability, creativity, knowledge of science process, and scientific attitudes of the Philippine Science High School seniors, 1982-1983 - Torres, Elizabeth M.
To attain the purpose of this study, the researcher sought a school environment which matches the institutional characteristics of PSHS in terms of source of fund (government supported), faculty qualification, selection criteria for admission and commitment to quality education. These criteria were applied to the University of the Philippines Integrated School (UPIS) and yielded correspondence with the PSHS except in emphasis on a science based curriculum. Thus, the UPIS was taken as the counterpart of the PSHS but with a non-science-based curriculum.
Keywords: High school seniors -- Philippines -- Quezon City -- Attitudes